Benzamides Substituted with Quinoline-Linked 1,2,4-Oxadiazole: Synthesis, Biological Activity and Toxicity to Zebrafish Embryo - Bin-Long Sun; Ying-Ying Wang; Sen Yang; Min-Ting Tu; Ying-Ying Shao; Yi Hua; Yi Zhou; Cheng-Xia Tan (Molecules, 2022)
To develop new compounds with high activity, broad spectrum and low-toxicity, 17 benzamides substituted with quinoline-linked 1,2,4-oxadiazole were designed using the splicing principle of active substructures and were synthesized. The biological activities were evaluated against 10 fungi, indicating that some of the synthetic compounds showed excellent fungicidal activities. For example, at 50 mg/L, the inhibitory activity of 13p (3-Cl-4-Cl substituted, 86.1%) against Sclerotinia sclerotiorum was superior to that of quinoxyfen (77.8%), and the inhibitory activity of 13f (3-CF3 substituted, 77.8%) was comparable to that of quinoxyfen. The fungicidal activities of 13f and 13p to Sclerotinia sclerotiorum were better than that of quinoxyfen (14.19 mg/L), with EC50 of 6.67 mg/L and 5.17 mg/L, respectively. Furthermore, the acute toxicity of 13p was 19.42 mg/L, classifying it as a low-toxic compound.